European Higher Education and the Internal Market Tensions Between European Policy and National Sovereignty - Sin, Cristina; Tavares, Orlanda; Cardoso, Sónia; J. Rosa, Maria (Issues in Higher Education, 2018)
XXII, 383 p. 3 illus.